2022
DOI: 10.1108/aeat-06-2022-0150
|View full text |Cite
|
Sign up to set email alerts
|

Bio-inspired optimization of leading edge slat

Abstract: Purpose The high lift devices are effective at high angle of attack to increase the coefficient of lift by increasing the camber. But it affects the low angle of attack aerodynamic performance by increasing the drag. Hence, they have made as a movable device to deploy only at high angles of attack, which increases the design and installation complexities. This study aims to focus on the comparison of aerodynamic efficiency of different conventional leading edge (LE) slat configurations with simple fixed bioins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Incorporating an internally blowing flap and a leading edge slat can significantly improve the overall force coefficients (Burnazzi and Radespiel 2014). Bio-inspired leading-edge slats' performance was tested using the cambered aerofoil (Mandadzhiev et al 2017;Raj et al 2023). Javur et al (1982) demonstrated that the off-design performance of an axial flow fan was improved by a slat attachment, while Chen et al (2012) reported an improvement in off-design aerodynamic performance of fluid machinery by using slat augmentation.…”
Section: Introductionmentioning
confidence: 99%
“…Incorporating an internally blowing flap and a leading edge slat can significantly improve the overall force coefficients (Burnazzi and Radespiel 2014). Bio-inspired leading-edge slats' performance was tested using the cambered aerofoil (Mandadzhiev et al 2017;Raj et al 2023). Javur et al (1982) demonstrated that the off-design performance of an axial flow fan was improved by a slat attachment, while Chen et al (2012) reported an improvement in off-design aerodynamic performance of fluid machinery by using slat augmentation.…”
Section: Introductionmentioning
confidence: 99%